Telematics in Inland Navigation - Jarmila Sosedova; Jan Slesinger; Miroslav Bariak (Communications - Scientific letters of the University of Zilina, 2008)
One of the goals of EU transport policy is the implementation of integrated control systems to control transport processes in all means of transport, including the systems for water transportation. Recent deployment of information and communication technologies on inland waterways brings noticeable impact in security and efficiency of transport. Based on this, the European Council and Parliament issued the directive concerning harmonized River Information Services (RIS) on inland waterways around European Union Member States. Its aim is the harmonized implementation of information and communication systems on the network of European inland waterways.